Divergent Synthesis of Substituted Amino-1,2,4-triazole Derivatives - Zhao, Fenghai; Singh, Thishana; Xiao, Yumei; Su, Wangcang; Yang, Dongyan; Jia, Changqing; Li, Jia-Qi; Qin, Zhaohai (Synthesis, 2021)
A divergent efficient assembly of disubstituted 1,2,4-triazoles was established by cyclization of readily accessible N′-nitro-2-hydrocarbylidene-hydrazinecarboximidamides with moderate to excellent yields under mild reaction conditions. This divergent synthetic strategy was achieved simply by varying the reaction conditions. Under acidic conditions, amino-1,2,4-triazoles were obtained by an intramolecular redox reaction involving the NO2 group. Control experiments and DFT studies revealed that this transformation proceeds via an intramolecular 1,3-hydride transfer pathway leading to HNO2 elimination. Under neutral conditions with water as the solvent, nitroimino-1,2,4-triazoles were obtained by oxidative intramolecular annulation under air.
Keywords: 1,2,4-triazoles; divergent synthesis; redox chemistry; cyclization; heterocycles